Cloud cover and cloud types in the Eurasian Arctic in 1936–2012. (1st July 2019) - Chernokulsky, Alexander; Esau, Igor
Abstract: The Arctic is a cloudy place. It has been recognized that the Arctic cloud cover is sensitive to different climatic factors such as sea ice extent and atmospheric circulation indices. Moreover, several influential climate feedbacks, for example, the summertime cloud‐radiation feedback, have been recognized. Yet, the cloud cover studies were limited in time to the satellite era observations and fragmentary data sets from meteorological stations. Here, we present the complete long‐term cloud records from 86 meteorological stations in the Eurasian Arctic. The stations are located on the coast and islands of the region from the Barents to Chukchi Seas. Thus, this study is complementing and extending the study by Chernokulsky et al . (2017) where the cloud data from the Norwegian through Kara Seas were presented. Our data set comprises the entire period of observations at each station. However, we present the area‐wide analysis only over the historical period of 1936–2012 when there were sufficient density of stations and cloud records for the coherent analysis. The total cloud cover, which on multiannual average constitutes 69–74% in different areas, increases in the warmer periods. The strongest increase is found in the convective cloud cover, particularly in the Chukchi Sea. We observe statistical evidence of transition between stratiform and convective cloud types. The cloud characteristics reveal the strongest correlations with the Atlantic circulation indices and the sea ice concentration in all Eurasian Arctic areas. The correlations with the Pacific circulation indices are much less significant. The obtained cloud data sets disclose much smaller scale features and variability, which deserve further research. Abstract : We present the long‐term dataset for cloud characteristics based on visual observations from 86 meteorological stations in the Eurasian Arctic from the Barents to Chukchi Seas. The total cloud cover increases in the warmer periods and the transition between stratiform and convective cloud types occurs in the recent warming. The cloud characteristics have the strongest correlations with the Atlantic circulation indices and the sea ice concentration while the correlations with the Pacific circulation indices are less significant.